2020
DOI: 10.1002/cam4.2958
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported symptoms associated with quality of life during chemo‐ or immunotherapy for bladder cancer patients with advanced disease

Abstract: Background: Bladder cancer (BC) patients with advanced disease have poor outcomes. The use of patient-reported outcomes (PROs) could lead to improvements in symptom management and hence quality of life (QoL). The aim of this study is to report correlations between selected PROs and QoL and thus to present symptoms that influence QoL. Identification of these symptoms during treatment can lead to earlier symptom management and thus secure improvements in QoL. Methods: BC patients in chemo-or immunotherapy for lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Despite the importance of HRQoL of patients following immunotherapy, it has only received some limited, recent research attention [ 21 , 22 ]. One noticeable gap is that less HRQoL-focused research has been performed regarding cancer immunotherapy purely due to the treatment’s relative novelty.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of HRQoL of patients following immunotherapy, it has only received some limited, recent research attention [ 21 , 22 ]. One noticeable gap is that less HRQoL-focused research has been performed regarding cancer immunotherapy purely due to the treatment’s relative novelty.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer patients, it is common for psychological symptoms associated with the course of the disease to appear, such as anxiety, depression, insomnia, fatigue, and a poorer quality of life ( Mock et al, 2000 ; Satin et al, 2009 ; Corbett et al, 2016 ; Kuhnt et al, 2016 ; Zhou et al, 2017 ; Pitman et al, 2018 ; De Mol et al, 2020 ; Erim et al, 2020 ; Park et al, 2020 ; Taarnhøj et al, 2020 ; Yun et al, 2021 ). Among the different interventions developed to reduce these symptoms in cancer patients, acceptance and commitment therapy performs better than other interventions (such as cognitive-behavioral therapy) as it focuses on improving the psychological flexibility of patients, which causes improvements in associated symptoms, such as those mentioned above ( Feros et al, 2013 ; Arch and Mitchell, 2016 ; Aguirre-Camacho and Moreno-Jiménez, 2017 ; Bas and Dirik, 2019 ; González-Fernández and Fernández-Rodríguez, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In cancer patients, it is common to observe certain impairments as a consequence of the disease and its treatments. The most frequent psychological symptoms are anxiety (10–18%) and depression (11–20%), which, in addition, are consistently related to a worse quality of life in this group of patients ( Satin et al, 2009 ; Kuhnt et al, 2016 ; Pitman et al, 2018 ; De Mol et al, 2020 ; Erim et al, 2020 ; Park et al, 2020 ; Taarnhøj et al, 2020 ). Fatigue, understood as a subjective state of emotional and physical fatigue that interferes with the patient’s normal functioning, appears in up to 60% of cancer patients, while sleep disturbances, both in the form of insomnia, as in terms of difficulties when falling asleep, and maintaining sleep, is also observed in a high number of patients, in a range between 18 and 68% ( Mock et al, 2000 ; Corbett et al, 2016 ; Zhou et al, 2017 ; Yun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of bladder cancer patients, the PRO-CTCAE showed significant correlation with the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30, especially for psychological measures. 134 Despite BCG's long-standing historical efficacy for patients with NMIBC, its administration may negatively affect QOL by causing discomfort and functional impairment. While the majority of patients complete the 6-cycle induction course, a substantial number of patients discontinue maintenance due to symptoms negatively affecting their QOL.…”
Section: Recognition and Management Of Iraesmentioning
confidence: 99%